Low‐temperature cofired ceramic planar helical filter with single‐sided transmission zeros. Issue 19 (1st September 2014) - Wu, Yafen; Che, Wenquan; Chin, Kuo‐Sheng; Chang, Kuang‐Ching; Feng, Wenjie
Abstract : A planar low‐temperature cofired ceramic helical bandpass filter with a compact size is presented. The proposed filter is constructed from short‐circuited λg /4 helical resonators, while the size is reduced significantly by winding resonators vertically. Two single‐sided transmission zeros can be created by the proposed mixed electric and magnetic coupling structure. A prototype with size of 6.2 × 4 mm 2 (0.049 × 0.032 λg 2 ) has been fabricated for demonstration. The measured fractional bandwidth is 5.9% at 0.845 GHz, and two transmission zeros are observed at 0.90 and 1.07 GHz.